2017
DOI: 10.1089/cap.2016.0199
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Therapy for Violent and Aggressive Male Youth: An Open-Label Trial

Abstract: Micronutrient therapy appeared well tolerated, with a favorable side effect profile. It appeared effective in the reduction of parent-reported aggressive and violent behaviors, and showed improvement in family functioning and HRQoL in male youth after 16 weeks. Further research in the form of a double-blinded, randomized controlled trial is required to verify these initial positive observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 46 publications
1
8
1
Order By: Relevance
“…And consistent with the results of (Hambly et al, 2017) who study micronutrient therapy for violent male aged 4 -14 who displayed ongoing violent and aggressive behaviors received micronutrient intervention containing ascorbic acid (vitamin C), vitamin E, biotin, pyridoxine (vitamins B6), zinc and selenium, in a 16-week. Participants were examined for changes in violent and aggressive behaviors that measured by using the Children's Aggression Scale, and the result showed that micronutrient therapy significantly improved in parent-reported.…”
Section: Discussionsupporting
confidence: 74%
“…And consistent with the results of (Hambly et al, 2017) who study micronutrient therapy for violent male aged 4 -14 who displayed ongoing violent and aggressive behaviors received micronutrient intervention containing ascorbic acid (vitamin C), vitamin E, biotin, pyridoxine (vitamins B6), zinc and selenium, in a 16-week. Participants were examined for changes in violent and aggressive behaviors that measured by using the Children's Aggression Scale, and the result showed that micronutrient therapy significantly improved in parent-reported.…”
Section: Discussionsupporting
confidence: 74%
“…This study aimed to determine whether change in individual nutrient levels could predict strength of response to a nutrient intervention. Others have proposed that change in serum nutrient levels is an important component associated with outcome (Hambly et al, 2017; Kimball, Mirhosseini, & Rucklidge, 2018); however, what has never been investigated is whether the change as measured in peripheral blood is necessary for treatment benefit to occur.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be that when a broad spectrum of nutrients is provided, the effect of a change in any one nutrient becomes less important. The studies that have shown a decrease in copper alongside clinical improvement have given only a few nutrients (<10), zinc in reasonably high doses, and no copper (Hambly et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A broad spectrum of minerals and vitamins (sometimes combined with omega 3s) can reduce aggression and violent incidents. The results have been reported across a range of populations, from aggressive children to incarcerated adults (Gesch et al, 2002;Hambly et al, 2017;Kaplan et al, 2004;Kaplan, Hilbert, et al, 2015;Rucklidge et al, 2018;Schoenthaler et al, 1997;Schoenthaler & Bier, 2000;Tammam et al, 2016;Zaalberg et al, 2010). The earliest randomized trial was more than 20 years ago, when researchers conducted a fully blinded three-month RCT in 62 incarcerated youth aged 13-17.…”
Section: Aggressionmentioning
confidence: 99%